IMPLEMENTASI TEORI HUMANISTIK DENGAN PENDEKATAN ACTIVE LEARNING DALAM PEMBELAJARAN BAHASA ARAB DI MTS MAMBAUS SHOLIHIN SUCI MANYAR GRESIK - Pengelola, Pengelola; Romadhon, Nisfi (Tasyri’: Jurnal Tarbiyah – Syari’ah Islamiyah, 2025)
In a learning process, there are many approaches, strategies, and methods that educators must master to improve student learning achievement; there is a lack of awareness of the importance of learning Arabic, making this material less popular with some students in several Islamic Educational Institutions today. This study aimed to determine the Implementation of Arabic Language Learning Through Humanistic Theory with an Active Learning Approach at MTs Mambaus Sholihin Manyar Gresik, the learning steps, and the benefits of implementing humanistic theory in Arabic language learning. This research process uses qualitative research, with the data collection process using participant observation, in-depth interviews, and documentation. Triangulation techniques and peer checking obtain data validity. The data analysis model includes analysis of each case and cross-case. The results of the study indicate that the humanistic theory with an active learning approach applied at MTs Mambaus Sholihin, the author concludes that: (1) The learning process by implementing humanistic theory with an active learning approach at MTs Mambaus Sholihin is manifested in several components that influence each other (2) learning steps can be developed into eight stages. (3) The benefits of learning Arabic by implementing humanistic theory with an active learning approach at MTs Mambaus Sholihin include the potential of students to develop in a balanced and more optimal manner (cognitive, affective, and psychomotor) because the learning process contains elements of communicative interaction between educators and students and between other peers.